Liposomal amphotericin B as a treatment for human leishmaniasis - Balasegaram, Manica (Informa UK, Ltd., 2012)
INTRODUCTION: Leishmaniasis is a parasitic disease transmitted by phlebotomine sandflies. Between 700,000 and 1.2 million cases of cutaneous leishmaniasis and between 200,000 and 400,000 cases of visceral leishmaniasis (VL), which is fatal if left untreated, occur annually worldwide. Liposomal amphotericin B (LAMB), alone or in combination with other drugs, has been extensively studied as VL treatment, but data on routine field use are limited, and several challenges to patients' access to this life-saving drug remain. AREAS COVERED: This article provides a review of clinical studies on LAMB for VL and other forms of leishmaniasis. The current development of generic versions of LAMB and related challenges are also discussed. EXPERT OPINION: LAMB proved to be highly efficacious and safe in over 8000 VL patients treated by MÉdecins Sans Frontières in South Asia, and its use was feasible even at primary healthcare level. Despite requiring higher doses, LAMB is the drug of choice to treat vulnerable groups (e.g., pregnant or HIV positive) and relapsing VL patients in East Africa. LAMB should be included in national VL guidelines and registered in all VL endemic countries. Its cost should be further reduced and regulatory pathways to prove bioequivalence for generic LAMB products should be implemented.